Spiritual culture of a teacher as a part of his professional culture. - Timoshchuk А.V (Kharkov National Pedagogical University, 2011)
The essence of professional and spiritual culture of a teacher is described, the theoretical aspects of these concepts and the relation between them are characterized; the tasks of the formation of spiritual culture of a future teacher during professional training and the basic requirements for the profession are identified. It is indicated that professional training of a future teacher with a focus on spiritual development is the prerequisite for effective educational activities.